A parent intervention with a growth mindset approach improves children's early gesture and vocabulary development. Issue 4 (18th January 2019) - Rowe, Meredith L.; Leech, Kathryn A.
Abstract: Socioeconomic disparities in children's early vocabulary skills can be traced back to disparities in gesture use at age one and are due, in part, to the quantity and quality of communication children are exposed to by parents. Further, parents' mindsets about intelligence contribute to their interactions with their children. We implemented a parent gesture intervention with a growth mindset component with 47 parents of 10‐month‐olds to determine whether this approach would increase parents' use of the pointing gesture, infants' use of pointing, and child vocabulary growth. The intervention had an effect on parent gesture such that by child age 12‐months, parents who received the intervention increased in their pointing more than parents in the control condition. Importantly, the intervention also had a significant effect on child gesture use with parents. There was no main effect of the intervention on child vocabulary. Further, the effect of the intervention on pointing was stronger for parents who endorsed fixed mindsets at baseline, and had an added benefit of increased vocabulary growth from 10–18 months for children of those parents who endorsed fixed mindsets. Incorporating growth mindset approaches into parenting interventions is encouraged. Abstract : We implemented a parent gesture intervention with a growth mindset component with 47 parents of 10‐month‐olds to determine whether this approach would increase parents' use of the pointing gesture, infants' use of pointing, and child vocabulary growth. The intervention had an effect on parent gesture such that by child age 12‐months, parents who received the intervention increased in their pointing more than parents in the control condition. Importantly, the intervention also had a significant effect on child gesture use with parents. Further, the effect of the intervention on pointing was stronger for parents who endorsed fixed mindsets at baseline, and had an added benefit of increased vocabulary growth from 10–18 months for children of those parents who endorsed fixed mindsets.